RELEVANCE OF INFORMATION AND CONTRACTUAL MODALITY OF AESTHETIC MEDICINE: A COMPARATIVE ANALYSIS BETWEEN SPANISH AND POLISH CASE-LAW - Rymkiewicz, Dominika (Review of European and Comparative Law, 2018)
Aesthetic medicine has been developing at a fast pace in recent years. It is necessary and ethical for anyone who undergoes any of these treatments to receive complete information on its implementation methods, as well as its consequences and adverse effects. Only once the person who would be affected by these procedures obtains truthful and impartial information, can he or she provide a legally binding consent to undergo a procedure. Thus, the information received by the patient plays a crucial role since it underlies the subject’s decision concerning the treatment.